Instructional Scaffolding in Online Content-based Instruction: Intentions of Teachers’ Scaffolding - Zahra Kamrani; Zia Tajeddin; Minoo Alemi (Journal of Modern Research in English Language Studies)
The emerging interest in scaffolding as a dynamic, multifaceted, and evolving construct has mounted over the last decades due to its impact on teachers’ professional development and students’ learning. The present paper adopted conversation analysis to analyze scaffolding intentions in content-based instruction (CBI) based on Van de Pol et al.’s (2010) framework of scaffolding intentions, which includes direction maintenance, cognitive structuring, reduction of the degrees of freedom, recruitment, and frustration control. Through convenience sampling, four science teachers in English-medium CBI were selected, and the videotaped recordings of 12 hours of their online classroom instruction were transcribed and analyzed. The findings indicated that scaffolding intentions mostly pertain to enhancing students’ cognitive structuring, controlling their frustration, and promoting their engagement in the learning process. The findings showed that the cognitive load of learning concepts was one of the main determiners of teachers’ scaffolding. Also, various activities to recruit interest were used by the teachers to provide scaffolding. The findings evidenced that teachers’ interactional and instructional techniques were mostly centered on directing students towards the pedagogical aims and engaging them in the various activities at hand to call students’ attention to the applicability of science matters in the real-life or personal experience. In this study, developing self-supporting and self-reflecting strategies was found to be demanding for the teachers. These findings have implications for the teachers and teacher educators to heighten teachers’ awareness of scaffolding in CBI classes to enact more effective teaching.